Application of the compartmental model to the gas–liquid precipitation of CO2‐Ca(OH)2 aqueous system in a stirred tank. Issue 1 (10th November 2016) - Zhao, Wenli; Buffo, Antonio; Alopaeus, Ville; Han, Bing; Louhi‐Kultanen, Marjatta
Abstract : A compartmental model is formulated to assess the influence of fluid dynamics on the gas–liquid precipitation of CO2 (g)‐Ca(OH)2 (aq) system in a stirred tank reactor. The model combines the description of the flow field with several sub‐models, namely gas to liquid mass transfer, chemical reaction, precipitation, and population balance for both gas bubbles and solid crystals. The modeling predictions, including the average volumetric mass transfer coefficient, the concentration of calcium ions, the pH of the solution and the Sauter mean diameter of the final crystal products are eventually compared with measurements carried out on a pilot‐scale stirred tank. The results show that the local volumetric mass transfer rate and the final particle sizes distribution of the crystals are significantly affected by high local turbulence near the impeller. The local information simulated by the compartmental model, such as mass transfer rate, gas hold up and particle size of crystals and bubbles are important for the design and scaling of gas–liquid precipitators, with a computational time which is of several orders of magnitude faster than a full CFD computation. © 2016 American Institute of Chemical Engineers AIChE J, 63: 378–386, 2017